2005
DOI: 10.1002/chem.200401151
|View full text |Cite
|
Sign up to set email alerts
|

Fluorous Base‐Pairing Effects in a DNA Polymerase Active Site

Abstract: We describe selective "fluorous" effects in the active site of a DNA polymerase, by using nucleotide analogues whose pairing edges are perfluorinated. The 5'-triphosphate deoxynucleotide derivatives of DNA base analogues 2,3,4,5-tetrafluorobenzene ((F)B) and 4,5,6,7-tetrafluoroindole ((F)I), as well as hydrocarbon controls benzene (B) and indole (I), were synthesized and studied as substrates for the DNA Polymerase I Klenow fragment (KF exo-). Modified nucleotides were present in the DNA template or were suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Selective pairing of the fluorinated bases with one another in duplex DNA was observed. DNA replication has subsequently been examined using polyfluorinated nucleotide analogues as substrates [128]. A DNA polymerase active site was able to process the polyfluorinated nucleotides more efficiently than the corresponding hydrocarbon pairs, demonstrating hydrophobic selectivity of fluorinated bases for other fluorinated bases.…”
Section: Amino Acids and Proteins With Fluorinated Patchesmentioning
confidence: 99%
“…Selective pairing of the fluorinated bases with one another in duplex DNA was observed. DNA replication has subsequently been examined using polyfluorinated nucleotide analogues as substrates [128]. A DNA polymerase active site was able to process the polyfluorinated nucleotides more efficiently than the corresponding hydrocarbon pairs, demonstrating hydrophobic selectivity of fluorinated bases for other fluorinated bases.…”
Section: Amino Acids and Proteins With Fluorinated Patchesmentioning
confidence: 99%
“…A DNA polymerase active site was able to process the polyfluorinated base pairs more effectively than the analogous hydrocarbon pairs, demonstrating hydrophobic selectivity of polyfluorinated bases for other polyfluorinated bases. 23 Incorporation of non-natural polyfluorinated bases, capable of enhanced (or ''hyper''-) hydrophobic interactions, expands the genetic alphabet beyond the natural one used in replication, thus illustrating the emerging role of F-compounds in developing chemistry, including constitutional dynamic ''bio''chemistry that lies well ''beyond'' nature.…”
Section: Designing Abiotic Self-assembling and Selection Processesmentioning
confidence: 99%
“…The substitution resulted in bright probes which were still able to form complementary complexes. It was also demonstrated that polymerase enzymes can interact and use these nucleoside analogues (Kool 2000;Lai and Kool 2005;Krueger and Kool 2009). This discovery inspired further designing new bases and base pairs as alternative genetic code that vary in shape/size and testing whether they function as normal base pairs.…”
Section: Substitution Of the Entire Nucleobase With A Fluorescent Molmentioning
confidence: 96%